Teens and preteens, what do they see and why? (Journal of Parents and Teachers, 2014)
The article offers expert opinions on the reasons why people watch certain television programs. Subsequently, and through surveys, it is known the reasons teens and preteens themselves give when asked why they watch TV (entertainment, emotional experience or identity formation) and which programs they prefer (Grey´s Anatomy, Hannah Montana). Finally, some activities are proposed in order to work with text and series in the classroom.
Keywords: Survey; TV series; opinion.